(3GdgHI GdLRjdI aj TQM GdhSjdIs - (3MHjH Gddg Hf GdCejf Hf eMeO Hf jadL GdSbQGhi GdMSfjs
(3ChdgG (B:s
(3GdMeO ddg Ydi JhMjOg , hGdUdGI hGdSdGe Ydi NjQ YHjOg , hHYO adeG ChdY GdfGS HhSjdI GdSYGOI , JCdja GdeNJGQ Hf Hhfg WdH efi HYV ef jSJLdjgG Cf CcTa dg HGdTQM Yf eYGfjgG aCLHJg dPdc hSejJg GdgHI s
(3BNQgG (B:s
(3hCXgQ Cfg CYR efge hCcHQ , hGSJYHGO bdhHge hESJMGdJgG hGdMeO ddg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV YHGQGJgG HGdMeQIs
(3MhGagG eJbUaI s
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdJhMjO hGdedd hGdfMds